Spermatological Characterization of the Cestode Meggittina gerbilli (Cyclophyllidea: Catenotaeniidae), a Parasite of Gerbils, Gerbillus gerbillus and Gerbillus campestris (Rodentia: Muridae) in Tunisia - Faouzi Aouina; Hichem Kacem; Natalia Martín-Carrillo; Pilar Foronda; Jordi Miquel (Animals, 2023)
Ultrastructural characters of spermiogenesis and the mature spermatozoon of the cestode Meggittina gerbilli (Cyclophyllidea: Catenotaeniidae), a parasite of the Lesser Egyptian gerbil (Gerbillus gerbillus) and the North African gerbil (Gerbillus campestris) (Rodentia: Muridae) in the Djebel Dahar (South of Tunisia), were studied using transmission electron microscopy. The spermiogenesis of M. gerbilli is of Bâ and Marchand’s type III, which is mainly characterized by a proximodistal fusion of a single flagellum with a cytoplasmic extension. In this catenotaeniid, the proximal fusion is preceded by a 90° rotation of the flagellum. The spermatozoon is a Levron et al. type VI, which presents a single axoneme with the 9 + ‘1’ trepaxonematan pattern, a periaxonemal sheath, two crest-like bodies, twisted cortical microtubules, and a spiraled nucleus. The obtained results show similarities with the remaining studied catenotaeniids, namely Catenotaenia pusilla and Skrjabinotaenia lobata. The results are compared and discussed according to several characteristics found in the catenotaeniids and other studied cyclophyllideans.